إسهامات الأنشطة الرياضية الترويحية في الحد من الضغوط النفسية لدى أعوان محاغفظة الغابات - بوراس, عابد (Institut d'Éducation Physique et Sportive - Mostaganem 2024/2025, 2025)
هدفت هذه الدراسة التي بين أيدينا إلى محاولة معرفة إسهامات الأنشطة الرياضية الترويحية في الحد من الضغوط المهنية لدى أعوان(الحراس) محافظة الغابات،لأجل ذلك اتبعنا المنهج الوصفي ،حيث تكونت عينة من 22 عونا، واستعملنا أداة الاستبيان ،واستخدمنا لتحويل البيانات إلى نتائج إحصائية معامل(الصدق،الثبات،معامل الارتباط البسيط لبيرسون). جاءت أهم نتائج الدراسة ان أعوان (حراس) محافظة الغابات يعانون من ضغوط مهنية ، وأن كل الأعوان يمارسون النشاطاتهم الرياضية كونها تساعد على المحافظة على صحتهم النفسية و الجسدية ،اما اهم الاقترحات و التوصيات فتمثلت بداية بالاهتمام بالأنشطة الرياضية الترفهية ، حيث ذات أهمية نفسية للأعوان ،مساهمة الإدارة في دعم الأنشطة الترويحية لتقوية العلاقة بينهم مما يعكس إيجابا على تنسيق العمل. // // // // This study aimed to explore the contributions of recreational sports activities in reducing occupational stress among forest conservation agents (guards). To achieve this, the descriptive method was adopted, and the sample consisted of 22 agents. A questionnaire was used as the data collection tool, and the data were analyzed using statistical methods including validity, reliability, and Pearson's simple correlation coefficient. The main findings of the study revealed that forest conservation agents (guards) suffer from occupational stress and that all agents engage in recreational sports activities, as they help maintain their physical and mental health. Among the most important suggestions and recommendations were giving more attention to recreational sports activities due to their psychological importance for the agents, and encouraging administrative support for these activities to strengthen interpersonal relationships, which would positively reflect on work coordination.
MEPS-2025-22
Keywords: الأنشطة الرياضية الترويحية- الضغوط المهنية- أعوان محافظة الغابات // // : Recreational sports activities - Occupational stress -Forest conservation agents.